Entrapping of inclusions within carbon nanotubes during catalytic decomposition of C2H4 on a “thick” nickel film - Li, Feng Ji (2014)
To understand the formation mechanism of catalyst inclusions in carbon nanotubes, multi-walled carbon nanotubes were grown via catalytic decomposition of C2H4 on a 50-nm-thick nickel film at 725 C. Atomic force microscopy, glancing incidence X-ray diffraction, field emission scanning electron microscopy, and high resolution transmission electron microscopy were employed to examine the evolution of the nickel film and the structure of the nanotubes. It was found that pretreating of the nickel film resulted in lots of small nanoparticles extruding on the surface, among big ones, serving as seeds for the growth of tubes. The inner walls of a few tubes were sealed internally by multiple elongated “beads-like,” “bullet-shaped” or “needle-shaped” nickel inclusions. The inclusions retained the face-centered-cubic crystalline structure of the as-sputtered nickel film. The entrapping of nickel inclusions is explained by a continuous tip growth model. A conservative upper limit of the nickel layer thickness (50 nm) was estimated for growing high purity carbon nanotubes.